ANALISIS MAQASHID SYARIAH DAMPAK KEBERADAAN MINIMARKET MODERN TERHADAP USAHA DAGANG TRADISIONAL DI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT - Nasution, Ridhatillah Rosamalinda; Suryani, Ermi; Fadilah, Hafid (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
Competition between small stalls and minimarkets is a phenomenon that is familiar to our ears, especially in the city of Bogor. Minimarket growth has mushroomed in various locations and has even penetrated into densely populated settlements, especially in the era of globalization and the rapid development of science. This has led to competition between modern grocery stalls and minimarkets. both of them have similarities in selling daily necessities, only the service model and facilities are different. Several previous studies have stated that the turnover of traditional warungs has decreased since the emergence of franchised minimarkets which began to shift the position of traditional stalls in Pamijahan District. This study aims to analyze the impact of modern minimarkets on grocery stalls, as well as analyze it from the perspective of maqashid sharia. The research used descriptive qualitative method with a phenomenological approach, the research subject was in Pamijahan sub-district, Bogor district. The results of this study indicate that grocery shop business actors are affected by the existence of modern minimarkets seen from the decrease in daily turnover and the number of customers. And in the sharia perspective, the grocery shop operators do not feel affected because worship is carried out on their own volition, not because of something else.